2018
DOI: 10.1111/cfs.12439
|View full text |Cite
|
Sign up to set email alerts
|

Child protection practitioners: Including children in decision making

Abstract: This article presents findings from a study with 467 child protection practitioners in Australia to determine their practice responses and views on children's participation. The practitioners, recruited from 5 state jurisdictions, completed an online survey responding to case studies designed to determine the extent to which they would seek and include children's perspectives in decision making, and their confidence in talking to children. We report on practitioners' responses to a case study of a 5‐year‐old g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…However, they are less inclined to employ high-level participation practices such as giving children the opportunity to take part, or taking their opinions into consideration, in decision-making processes. These results are consistent with previous studies, which found that even when children are involved in the child welfare context, this involvement is very limited, and most of the time, their participation does not reach the point of actually influencing the decision that is being made (Bessell, 2011;Vis & Thomas, 2009;Woodman et al, 2018).…”
Section: Social Workers Use Of Participatory Practicessupporting
confidence: 93%
See 1 more Smart Citation
“…However, they are less inclined to employ high-level participation practices such as giving children the opportunity to take part, or taking their opinions into consideration, in decision-making processes. These results are consistent with previous studies, which found that even when children are involved in the child welfare context, this involvement is very limited, and most of the time, their participation does not reach the point of actually influencing the decision that is being made (Bessell, 2011;Vis & Thomas, 2009;Woodman et al, 2018).…”
Section: Social Workers Use Of Participatory Practicessupporting
confidence: 93%
“…Delgado et al () found that Portuguese child protection workers emphasized the importance of children's participation in decisions concerning their individual care plan. Woodman, Roche, McArthur, and Moore () reported that Australian child protection workers said they would speak with children and give weight to their perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Woodman et al’s (2018) survey regarding a case vignette of a 5-year-old girl with suspicious bruising and reports by the mother of domestic violence found that almost all child protection practitioners (97%) would speak to the child, and they felt the ability to talk to and value children’s views was an essential part of child protection work. In practice, participants discussing possibilities for child participation in youth care procedures were uncertain as to whether the child was actually heard during a meeting.…”
Section: Resultsmentioning
confidence: 99%
“…Child protection policy can have an important impact on individual child protection workers (Woodman and others, ). Policy that incorporates understandings that are responsive to the socio‐cultural and structural contexts of children's lives, and understands them as social actors with agency, can provide more beneficial responses to maltreatment, and focus more closely on their wellbeing and needs as children.…”
Section: Children Childhoods and Child Protection Policymentioning
confidence: 99%